POLIGAMI MENURUT HUKUM ISLAM DI TINJAU DARI UNDANG-UNDANG NO. 1 TAHUN 1974 - Muh. Nasir (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to understand the concept of polygamy in Islamic law by Act UU No. 1 of 1974 and to identify the weaknesses in the concept of setting polygamy Act UU No. 1 of 1974.Thisstudy aims to understand the concept of polygamy in Islamic law by Act No. 1 of 1974 and to identify the weaknesses in the concept of setting polygamy Act No. 1 of 1974. This research is the normative legal research done by examining the materials library, which the researchers used a methode of analysis in comparative law materials, comparing similarities and differences between polygamy according to Islamic law No. 1 of 1974. The results of this study indicate that the concept of setting according to Islamic law stated plainly on QS An-Nisa verse 3. So that polygamy should be based on the ability to do justice to his wives. While the concept of regulation according to Law no. 01 In 1974 based on Article 3 (2), Article 4, paragraph (1.2); Article 5 paragraph (1.2), and the transitional provisions of article 65 paragraph (1.2); listed also on Government Regulation no. 09 In 1975 On of Law. 01 Year 1974 On Marriage ie chapters 40-41, and there on the Compilation of Islamic Law (KHI) contained in Article IX of Chapter 55-59 and Chapter XII Part V Article 82. The flaws in the concept of polygamy Law setting. 01 year 1974 is still rife deskriminatif law because marriage laws still reflect the values ​​patriakhi, where the conditions prescribed by the law to her husband polygamous wife when there is a deficiency in good shape physically, mentally disturbed or wife's health, but it this does not apply to a husband who has a weakness as a wife. By Accordingly it is obvious that the policy of the State in this case the principle of equality for its citizens is still very ambiguous, and marriage law only emphasizes the complicated procedures that polygamy, but no marriage laws that govern how the welfare of the contents of the wives (women) to be polygamous.